Animal assisted education and social communication competency: systematic literature review - Sinéad Morgan (Discover Education)
Abstract The inclusion of canines in educational practice is becoming increasingly popular in Irish schools. The primary objective of this systematic literature review was to examine the emerging phenomenon regarding the application of certified canines in educational settings to support the social communication competency of children aged 4 to 14 years. Following a review of the literature it became apparent that, to date, little research has been conducted regarding the concept of animal assisted education and social communication competency. The results of this literature review clearly indicate that a certified therapy canine can positively enhance social skills. More specifically, this systematic literature review found that a therapy canine can positively influence the educational experience of all students inclusive of children with additional needs. Whilst the concept of animal assisted education has become an increasingly popular topic of research worldwide, it is clear that additional research pertaining to the benefits of therapy canines and the impact on a child’s educational experiences needs to be conducted. This paper supplements and enhances the current level of research in an endeavour to address the disparity in literature and investigate how the educational experience of a child is influenced by the bond established with a canine. The objectives of this review are to establish: Effective animal assisted education interventions in classroom settings for teaching children aged 4 years to 14 years, and social communication competency components that should be incorporated into the design of classroom-based animal assisted interventions for children. Whilst, the studies in this review have provided some evidence regarding the benefits associated with the application of animal assisted education within a classroom environment, it is apparent that there still exists a significant gap in literature in this area.